2014
DOI: 10.1007/s10646-014-1266-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties and toxicity of soils contaminated by mining activity

Abstract: This research is aimed at assessing the total content and soluble forms of metals (zinc, lead and cadmium) and toxicity of soils subjected to strong human pressure associated with mining of zinc and lead ores. The research area lay in the neighbourhood of the Bolesław Mine and Metallurgical Plant in Bukowno (Poland). The study obtained total cadmium concentration between 0.29 and 51.91 mg, zinc between 7.90 and 3,614 mg, and that of lead between 28.4 and 6844 mg kg−1 of soil d.m. The solubility of the heavy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Relative to natural processes such as volcanic activity and the weathering of rocks, anthropogenic activities such as mining, combustion of fossil fuels, metal production and other industrial and agricultural practices have been responsible for the increased Cd levels in the environment (Choppala et al 2014;Agnieszka et al 2014;Zhao et al 2015). Industrial emission, animal manures, sewage sludge and phosphate fertilizers are reported to have increased Cd concentrations in agricultural soils (Rao and Kashifuddin 2012).…”
Section: Level and Sources In Soilmentioning
confidence: 99%
“…Relative to natural processes such as volcanic activity and the weathering of rocks, anthropogenic activities such as mining, combustion of fossil fuels, metal production and other industrial and agricultural practices have been responsible for the increased Cd levels in the environment (Choppala et al 2014;Agnieszka et al 2014;Zhao et al 2015). Industrial emission, animal manures, sewage sludge and phosphate fertilizers are reported to have increased Cd concentrations in agricultural soils (Rao and Kashifuddin 2012).…”
Section: Level and Sources In Soilmentioning
confidence: 99%
“…EAFD can be reused in the production of castings and in metallurgy or for the production of Portland cement (Škvára et al 2002;Mymrin et al 2016). The EAFD can also be solidified with lime and concrete, in order to reduce the leachability of heavy metals, and landfilled (Andrés et al 1995;Hamilton and Sammes 1999). The composition of dust from the regeneration unit depends mainly on the type of molding sand and binder.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this species is the availability of seeds, rapid growth, sensitivity to environmental factors, including heavy metals, and low humidity requirements. Lepidium sativum is a recommended plant in many standards for biotoxicity test (Baumgarten and Spiegel 2004) and is used by many authors (Hoekstra et al 2002;Fuentes et al 2004, Barrientos et al 2012Baran et al 2014;Visioli et al 2014; Baran and Tarnawski 2015;Wierzbicka et al 2015;Praveen et al 2017;Khan et al 2018;Mañas and De las Heras 2018;Seneviratne et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was concluded that chemical extractions of metals from multi-contaminated soils did not provide enough information about their bioavailable fractions (Alexander 2000;Ehlers and Luthy 2003;Semple et al 2004;Harmsen 2007) and were not able to reflect the toxicity of all substances in soil, their synergic and antagonistic effects and their interactions with the soil matrix and organisms (Gruiz 2005). In this context, th e application of batteries of terrestrial ecotoxicity tests gained special relevance as complementary, inexpensive, simple and quick tools able to report realistic and nonoverestimated effects of contaminated sites to soil organisms (Leitgib et al 2007;Alvarenga et al 2008;Maisto et al 2011;Alvarenga et al 2012;Agnieszka et al 2014;Bes et al 2014;. At the same time, aquatic bioassays traditionally applied for the toxicity determination of aquatic pollutants (Lopez-Roldan et al 2012), industrial effluents (Riva et al 1993;Riva and Valles 1994;Riva et al 2007) or extracts of sediments (Pereira-Miranda et al 2011) were incorporated to assess the impacts of soil composition and runoffs on receiving waters (Loureiro et al 2005a;Rocha et al 2011).…”
Section: Introductionmentioning
confidence: 99%